2019
DOI: 10.3390/molecules24040687
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Amyloid Beta Aggregation and Deposition of Cistanche tubulosa Aqueous Extract

Abstract: Cistanche tubulosa aqueous extract (CTE) is already used as a botanical prescription drug for treating dementia in China. Our previous studies reported that phenylethanoid glycosides of CTE have anti-Alzheimer’s disease (AD) activity by inhibiting amyloid β peptide (Aβ) aggregation and deposition. However, recent studies considered that the phenylethanoid glycosides may be metabolized by intestinal bacteria, because all analysis results showed that the bioavailability of phenylethanoid glycosides is extremely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Red ginseng extract treatment significantly attenuated tubular damage, renal dysfunction and cell apoptosis and decreased ROS production in GM-induced rats ( Ansari et al, 2016 ). C. deserticola is an important traditional Chinese herbal for renal dysfunction treatment ( Chao et al, 2019 ). Decoction or medicinal liquor of this plant have been widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Red ginseng extract treatment significantly attenuated tubular damage, renal dysfunction and cell apoptosis and decreased ROS production in GM-induced rats ( Ansari et al, 2016 ). C. deserticola is an important traditional Chinese herbal for renal dysfunction treatment ( Chao et al, 2019 ). Decoction or medicinal liquor of this plant have been widely used.…”
Section: Discussionmentioning
confidence: 99%
“… Zhou et al (2019 ) found that the CH extract had antiapoptotic and antioxidant stress effects via inhibiting Aβ deposition and tau protein hyperphosphorylation and promoting synapse protection. Chao et al (2019 ) also discovered that the CH extract protected against AD by inhibiting Aβ peptide aggregation and deposition. In a clinical trial, AD patients were treated with CH capsules for 48 weeks.…”
Section: Natural Chinese Medicinementioning
confidence: 99%
“…Here, an efficient method for fabricating a cucurbituril-decorated, amine-modified diatom composite (CB–DA) is proposed, and the usefulness of this CB–DA composite for efficient sample enrichment and in situ nucleic acid preparation from pathogens and cells is demonstrated. The well-characterized process of amino functionalization of the surface of DE renders it a universal tool for targeting molecules, and cucurbit[6]uril (CB) has been introduced to enhance the ability of CB–DA composites to rapidly and efficiently adsorb molecules [3,16,17]. We have also verified that modification with 3-aminopropyl-methyl-diethoxysilane (APDMS) is more effective than traditional modification with 3-aminopropyl-triethoxysilane (APTES).…”
Section: Introductionmentioning
confidence: 99%